Avaliação do potencial biotecnológico do óleo da semente de Euterpe oleracea Mart. In vitro e In vivo e da sua nanoemulsão - BORGES, Katia Regina Assunção (2024)
Açaí seed oil, Euterpe oleracea Mart., is rich in unsaturated, saturated, monounsaturated and polyunsaturated fatty acids with anti-inflammatory, antioxidant, antimicrobial, antinociceptive, anticancer, antiatherogenic and healing activities. The açaí seed is a residue produced after pulping, being a source of bioactive compounds; therefore, it is necessary to study its pharmacological properties and contribute to sustainable development. The objective of this was to evaluate the biotechnological potential of Euterpe oleracea Mart seed oil. - in vitro and in vivo - and its Nanoemulsion. The fruits used were collected in the Maracanã Ecological Park (Parque da Juçara), in São Luís, Maranhão. Samples of the plant were collected between the months of August and November, and exsicata were prepared, duly stored in the Rosa Mochel Herbarium. Subsequently, the oil was extracted with n-hexane solvent in a Soxhlet extractor and analyzed as methyl esters, weighing 100 mg of the oil for analysis of the chromatographic profile by gas chromatography combined with mass spectrometry (GC-MS) to identify the fatty acids. and its physical-chemical characterization. After understanding the physical chemistry of the oil, the açaí seed oil nanoemulsion (NE- OEO) was developed based on the calculation of the Hydrophilic Lipophilic Balance (EHL), followed by stability analysis, chemical characterization and morphology. To determine the average particle size and polydispersity index, the formulations were evaluated using the dynamic light scattering technique (Nano ZS, Malvern Instruments Ltd., UK) and Zeta Potential on the Nano ZS equipment (Malvern Instruments Ltd., UK). Both the oil and NE-OEO showed physicochemical patterns within normal limits. In other words, the oil showed acidity (0.3556± 0.0003), humidity (1.25±1.64), saponification index (189 ± 1.04), refractive index (1.4707±0.00005 ), incineration residue (ash) (0.42±0.42) and density (0.928±0.00005). And NE-OEO showed normal patterns regarding droplet size (238.37 ± 3.96), homogeneity (PDI) (0.38 ± 0.38), Zeta potential (-9.59 ± 0.11), pH (7.0 ± 0.00.) and turbidity (0.267± 0.00). Regarding phenolic compounds, NE-OEO presented the highest concentration, 146.00 ± 0.259 mg, while the oil had 127.40 ± 0.449 mg EAG g-1 of phenolic compounds, and total flavonoids values were found to be 62.62 ± 0.930 mg for the oil and 113.80 ± 0.454 mg EQ g-1 for NE-OEO. The antioxidant activity was proven based on the EC50 evaluated in the DPPH and ABTS assay, with the oil being 375.698 μg/mL in DPPH, and nanoemulsions with a significantly lower EC50, equivalent to 229.845 μg/mL. The Trolox control presented an even lower EC50. In the ABTS test, the EC50 of açaí oil was 272.0208 μg/mL, while açaí oil nanoemulsions had an even lower EC50 value, measuring 201.2895 μg/mL. Trolox also showed a significantly lower EC50 compared to oil and NE-OEO, these data confirm the antioxidant capacity of the oil and its NE- OEO. In vitro analyzes were performed on the non-tumor cell lines mouse RAW 264.7 macrophages, and human HaCat keratinocytes and cervical cancer tumor lines SiHa (HPV-16) and HeLa (HPV-18). Non-tumor cell lines were treated with concentrations (7.8 to 1000 ug/mL) of the oil and NE-OEO for 24, 48 and 72 hours, and tumor cells were treated with concentrations (0.631 to 100 ug/mL) of the oil, made analyzes of cell viability, cell death, morphology, healing and clonogenicity. After in vitro analyses, the effect of açaí seed oil and NE-OEO was analyzed in vivo in female Swiss mice. The animals were treated with different concentrations of the oil (100, 200 and 300 mg/kg) and NE-OEO (100 mg/kg) applied 0.5 mL intraperitoneally every two weeks. Açaí seed oil is rich in polyphenols, flavonoids, saturated fatty acids (49.27%) and unsaturated fatty acids (50.73%), among which unsaturated fatty acids, 29.73% are monounsaturated, 20 .85% are polyunsaturated. Lauric, myristic (C14:0), palmitic, linoleic, and oleic fatty acids were the most identified. Viability assay with MTT ((3-(4,5- Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide)) demonstrated a cytotoxic effect of the oil on the SiHa (HPV-16) and HeLa (HPV- 18) and non-cytotoxic to the non-tumor cell lines HaCat, as well as the oil and NE-OEO were not cytotoxic to the non-tumor cell line RAW 264.7. Açaí seed oil induced morphological changes in HeLa and SiHa cells, inducing a reduction in cell viability, inhibiting cell migration and colony formation in cervical cancer cell lines. The annexin V-FITC assay showed cell death by early and late apoptosis at 24 and 48 hours after treatment with açaí seed oil. In in vivo experiments, the use of oil at a dose of 100, 200, 300 mg/kg and NE-OEO at a dose of 100 mg/kg were not toxic to the animals, in accordance with the normal patterns seen in the liver and kidney; Furthermore, it did not interfere with the behavior or weight of the animals, however, it induced an immunomodulatory response with a significant increase in IL10 and IL17. Our results suggest the biotechnological potential of the oil and NE-OEO in antitumor activity for cervical cancer, and in the development of colloidal systems for drug delivery. Furthermore, the use of açaí seed residue will contribute to both the local economy and sustainable development..